Development and validation of a multimedia educational resource to support recognition of aspiration-related signs in dysphagia among non-healthcare college students - Aroline Juan Amanna; Preetie Shetty Akkunje; Saranya Sarath; Vivek Gopinathan; Thejaswi Dodderi (Scientific Reports, 2026)
Abstract Aspiration in individuals with dysphagia is associated with serious health complications, including aspiration pneumonia and increased mortality. Despite its clinical significance, awareness of aspiration-related signs among the general public remains limited, leading to delayed recognition and intervention. This study aimed to develop and validate a multimedia educational resource to promote awareness of observable aspiration related signs during oral feeding among non-healthcare college students. A multi-phase developmental design was employed to appraise the aim. Key indicators of aspiration were identified through expert consensus using the nominal group technique, followed by structured script development. Content validity was established using the Educational Content Validation Instrument in Health, with a scale-level content validity index ≥ 0.90. The validated script was used to develop a 19.40-min multimedia educational video incorporating narration and visual content. The developed material was evaluated for overall suitability of information using the Suitability Assessment of Materials. Further validation of communication effectiveness was conducted using the Patient Education Materials Assessment Tool for Audiovisual Materials and the Centers for Disease Control and Prevention Clear Communication Index. A total of 44 participants, including healthcare professionals and non-healthcare college students, contributed across development and validation phases. The finalized multimedia educational resource demonstrated good suitability, with a mean Suitability Assessment of Materials score of 75%. The material achieved understandability scores exceeding 70% and actionability scores of 100% on the Patient Education Materials Assessment Tool. Communication clarity scores exceeded 90% on the Centers for Disease Control and Prevention Clear Communication Index, indicating high clarity and effectiveness. The present study developed and validated a multimedia educational resource which has high content validity, suitability, understandability, actionability, and communication clarity. Evaluation of its educational effectiveness must be undertaken in the subsequent phase of the research.